‘The devil is in the details’—Product-specific supply chain emissions are key to identifying optimal mitigation strategies in food systems - Navoda Liyana Pathirana; Michalis Hadjikakou (Environmental Research: Food Systems)
Greenhouse gas (GHG) emissions from the pre- and post-production stages of the food supply chain accounted for one-third of all food system emissions in 2021. The share of food system GHG emissions occurring outside the agricultural production stage has been increasing steadily in recent years, mirroring a rise in the consumption of more processed and packaged foods. This highlights the urgency of prioritising mitigation opportunities beyond those targeting the agricultural production stages. This perspective highlights the critical role of more granular food product-specific full supply chain GHG emission inventories in devising targeted mitigation strategies to more effectively and equitably reduce GHG emissions across the food system.